Energy and protein requirements for maintenance of dairy goats during pregnancy and their efficiencies of use - Harter, C. J. [UNESP]; Lima, L. D. [UNESP]; Silva, H. G. O. [UNESP]; Castagnino, D. S. [UNESP]; Rivera, A. R. [UNESP]; Resende, K. T. [UNESP]; Teixeira, I. A. M. A. [UNESP] (Amer Soc Animal Science, 2017)
It has been suggested that maintenance requirements are similar among animals of different physiological stages; however, important physiological changes occur in the maternal body during pregnancy. Therefore, the aim of this study was to determine the energy and protein requirements for the maintenance of pregnant dairy goats and to estimate their efficiency of energy and protein utilization for maintenance and pregnancy. We used 66 multiparous pregnant goats having 49.0 +/- 1.59 kg initial BW (around the third or fourth parturition) arranged in a randomized block design with a 3 x 3 factorial scheme including slaughter at different days of pregnancy (DOP; 80, 110, and 140 d) and feed restriction (0, 20, and 40% feed restriction). The comparative slaughter technique was used to estimate energy and protein maintenance requirements. Goats slaughtered at 140 DOP were subjected to digestibility trials at around 80, 110, and 140 DOP to estimate diet metabolizability and N balance (NBAL). Metabolizability decreased with feed restriction and was 63.3 +/- 2.16, 55.7 +/- 2.35, and 58.2 +/- 2.30% at 0, 20, and 40% of feed restriction, respectively (P < 0.01). There was no effect of DOP on NEm or the requirements of ME for maintenance (MEm), which were 197 and 315 kJ/kg empty body weight (EBW) 0.75, respectively, and the efficiency of ME utilization for maintenance (k(mE)) was 0.63. Similarly, DOP did not affect thedaily net protein requirements for maintenance (NPm) estimated using the comparative slaughter technique (1.38 +/- 0.512 g/kg EBW0.75; P = 0.003) or the NPm estimated using NBAL (2.49 +/- 0.594 g/kg EBW0.75; P < 0.01). The MP requirement for maintenance (MPm) estimated using the comparative slaughter technique was not affected by DOP and was 3.22 g MP/kg EBW0.75 (P < 0.01). The efficiency of MP utilization for maintenance (k(mP)) was 0.43. The efficiency of ME utilization for pregnancy (k(pE)) increased with the progress of pregnancy and was 0.058, 0.10, and 0.19 at 80, 110, and 140 DOP, respectively. Similarly, the efficiency of MP utilization for pregnancy (k(pP)) increased with DOP and was 0.12, 0.21, and 0.43 at 80, 110, and 140 DOP, respectively. There was no evidence that pregnancy affected NEm, MEm, NPm, and MPm or k(mE) and k(mP), which were also unaffected by DOP. However, kpE and kpP increased with pregnancy progress as a response to the physiological changes that pregnant females are subjected to.
Keywords: efficiency; metabolizable energy; metabolizable protein; nutritional demands